2021
DOI: 10.1016/j.jds.2020.04.014
|View full text |Cite
|
Sign up to set email alerts
|

The application of teledentistry for Saudi patients' care: A national survey study

Abstract: Background/purpose Teledentistry has emerged as a new communication tool in various dental disciplines around the world. The aim of this study was to investigate the applicability and reliability of teledentistry in the field of diagnostic dentistry and explore the perception of Saudi dentists of its benefits and concerns. Materials and methods An electronic survey with 40 questions was developed, validated and distributed electronically by email and social media channe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 25 publications
1
28
1
3
Order By: Relevance
“…Likewise, Boringi et al (2015) found that although most dentist students surveyed in their study had some knowledge about TD, they did not know how to inculcate it in practice in the future. In a study before the pandemic, Almazrooa et al (2020) reported that 50% of study participants have applied TD in their clinical practice. Therefore, it is important to expand and improve continuing TD education in the new generations to overcome this barrier.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Boringi et al (2015) found that although most dentist students surveyed in their study had some knowledge about TD, they did not know how to inculcate it in practice in the future. In a study before the pandemic, Almazrooa et al (2020) reported that 50% of study participants have applied TD in their clinical practice. Therefore, it is important to expand and improve continuing TD education in the new generations to overcome this barrier.…”
Section: Discussionmentioning
confidence: 99%
“…This concept becomes handy during the pandemic where many can get dental consultations and limited dental services remotely. Although dental professionals in Saudi Arabia believed that teledentistry would improve dental care, only 50% have applied it in their practice [ 4 , 26 ]. Despite that dentists are being skeptical about the application of teledentistry in dental care, teledentistry provides a safe venue for patients to get consultations and limited dental care during the pandemic in a safe and convenient manner.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we also found that 23% of the respondents were using telemedicine for teaching purposes during COVID-19 pandemic as it was proven in previous study that telemedicine can provide an addition to the conventional teaching methods in dental education. 15 In contrast, majority of the participants (82.6%) believe that telemedicine is not a substitute for face-to-face clinical visits. However, most of the participants are willing to adopt telemedicine as a part of their clinical practice.…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, in the event of COVID-19, we observed that majority of participants believe telemedicine can be used for consultation (72%) and follow-up ( Table 2 ), as observed in previous studies. 15 , 16 More than half of the respondents were familiar with the use of telemedicine. The use of personal smartphones was the preferred method for sharing patient’s images, radiograph and other telecommunications.…”
Section: Discussionmentioning
confidence: 99%